Tinjauan Komparatif atas Pemungutan Pajak Parkir Sebagai Salah Satu Obyek Pajak Kabupaten/Kota Dengan Beberapa Jenis Pajak Pusat - Nabitatus Sa'adah (Administrative Law and Governance Journal, 2018)
This study aims to know tax collection tax as one of the object of tax district/city with some type of tax center. The research method used in this research is normative legal research using qualitative analysis. The results showed that the Tax Income Tax Income Tax (PPh) and Value Added Tax (VAT) no the same effect. Keywords: Local Tax, Central Tax, Tax Object, Tax Collection